Health Financing and Expenditures in Balkan countries: the case of North Macedonia, Serbia, Bosnia and Herzegovina and Montenegro - Vasilevska, Hristina; Stojchevska, Monika; Stamenova, Aleksandra; Filipche, Milcho; Tozija, Fimka (Macedonian Medical Association = Македонско лекарско друштво, 2025)
Introduction. The health financing model and health spending should meet the population health needs. The aim of this paper is to analyze and compare the financing of the health systems in the selected Balkan countries: North Macedonia, Serbia, Bosnia and Herzegovina and Montenegro. Material and method. Data from World Health Organization HFA-DB and World Bank has been used as well as from Health in Action Reports for the selected countries. Desk review of official documents and websites of government and health institutions and the literature has been applied. Results. All countries had a socialist system in Yugoslavia and the same health system. The system was reformed later in the transitional period. The Bismarck model of mandatory health insurance is dominant in all countries with recent reforms in Montenegro. Montenegro introduced major health insurance reforms, shifting from a contributions-based system to a fully tax-funded system. In North Macedonia Healthcare spending is relatively low compared to European Union (EU) and Southeastern European countries, current health expenditure as % of GDP is 8.5% in 2021. The health expenditures in 2021 in Bosnia and Herzegovina with 9.6% of GDP, in Serbia 10.01%, and in Montenegro 10.5% are at the level of the average of the European region and EU countries (10.95%). Out-of-pocket (OOP) payments of health spending in 2021 are high, in North Macedonia is accounted for 41.7%, in Montenegro 38.08%, in Serbia 35,86% and in Bosnia and Herzegovina 30.71%. Conclusion. The financing of health systems in the Balkans has improved in the last decade following a series of transition reforms and socio-political challenges. However, inequalities in health systems between countries, as well as with EU countries, persist.
Keywords: Balkans; financing; health expenditures